2010
DOI: 10.1021/ol102121j
|View full text |Cite
|
Sign up to set email alerts
|

Palladium-Catalyzed Propargylic Substitution with Phosphorus Nucleophiles: Efficient, Stereoselective Synthesis of Allenylphosphonates and Related Compounds

Abstract: A new, efficient method is developed, based on a palladium(0)-catalyzed reaction of propargylic derivatives with various phosphorus nucleophiles, to produce allenylphosphonates and their analogues with defined stereochemistry in the allenic and the phosphonate moiety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
27
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(28 citation statements)
references
References 40 publications
1
27
0
Order By: Relevance
“…[2] Several approaches are available for their synthesis,a nd the most common ones are based on intramolecular cyclization of 1,4-aminoalcohols or derivatives. [6,7] Dehydration with phosphine and carbon tetrabromide in the presence of triethylamine, [5d] followed by direct addition of aldehydes to the crude reaction mixture,a nd then aqueous NaHCO 3 15 hours later, afforded the cyclic ene carbamates 5 in good to moderate yields (threestep process;T able 1). [4] Our interest in the use of boronic esters in cascade reactions [5] led us to consider their utility for the synthesis of enantioenriched 4,5-dihydro-1,3-oxazepin-2ones.T hese versatile intermediates led, through an unprecedented ring contraction reaction, to tetrasubstituted pyrrolidines,another family of major biological significance.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[2] Several approaches are available for their synthesis,a nd the most common ones are based on intramolecular cyclization of 1,4-aminoalcohols or derivatives. [6,7] Dehydration with phosphine and carbon tetrabromide in the presence of triethylamine, [5d] followed by direct addition of aldehydes to the crude reaction mixture,a nd then aqueous NaHCO 3 15 hours later, afforded the cyclic ene carbamates 5 in good to moderate yields (threestep process;T able 1). [4] Our interest in the use of boronic esters in cascade reactions [5] led us to consider their utility for the synthesis of enantioenriched 4,5-dihydro-1,3-oxazepin-2ones.T hese versatile intermediates led, through an unprecedented ring contraction reaction, to tetrasubstituted pyrrolidines,another family of major biological significance.…”
mentioning
confidence: 99%
“…[6,7] Dehydration with phosphine and carbon tetrabromide in the presence of triethylamine, [5d] followed by direct addition of aldehydes to the crude reaction mixture,a nd then aqueous NaHCO 3 15 hours later, afforded the cyclic ene carbamates 5 in good to moderate yields (threestep process;T able 1). [6,7] Dehydration with phosphine and carbon tetrabromide in the presence of triethylamine, [5d] followed by direct addition of aldehydes to the crude reaction mixture,a nd then aqueous NaHCO 3 15 hours later, afforded the cyclic ene carbamates 5 in good to moderate yields (threestep process;T able 1).…”
mentioning
confidence: 99%
“…However, a Scheme 18 Pyridine-directed palladium catalyzed phosphonylation of C(sp novel synthetic method was developed for the preparation of allenylphosphonates, applicable to biologically important natural product derivatives [129,130]. The method shown in Scheme 19 is based on a palladium-catalyzed propargylic substitution with phosphorus nucleophiles, and represents a new means of formation of the P-C bond.…”
Section: Pd-catalyzed Reactionsmentioning
confidence: 99%
“…The first catalytic procedure for Cu(I)-mediated coupling of aryl halides with H-phosphonate diesters, based on the Ullmann-type of chemistry, was described in 2003 by Buchwald [129,130] et al [132]. Since then, the number of applications of copper as a catalyst has steadily increased [133][134][135].…”
Section: Cu- Ni- and Other Metal-catalyzed Reactionsmentioning
confidence: 99%
“…However, the catalyst was less efficient and high catalyst loading was required (10-20 mol%). Recently, Kalek et al [15] reported the Pd-catalyzed propargylic substitution with phosphorus nucleophiles to the synthesis of allenylphosphonates [Scheme 1, Eq. (2)].…”
Section: Introductionmentioning
confidence: 99%